2021
DOI: 10.1088/1742-6596/2130/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation erosion damage of self-fluxing NiCrSiB hardfacings deposited by oxy-acetylene powder welding

Abstract: This paper comparatively investigates the cavitation erosion damage of two self-fluxing NiCrSiB hardfacings deposited via the oxy-acetylene powder welding method. Examinations were conducted according to the procedure given by ASTM G32 standard. In order to research cavitation erosion (CE), the vibratory apparatus was employed. The cavitation damaged surfaces were inspected using a scanning electron microscope, optical microscope and surface profilometer. The hardness of the A-NiCrSiB hardfacing equals 908HV w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…9a). Very short as well as the lack of incubation period was also noted by Li et al [53], who tested 316L steel, Wantang et al [54], who tested martensitic HNS steel and two CrNiMo stainless steel grades, Liu et al [55], who tested Cr-Mn-N steels, Szala [56], who tested the NiCrSiB hardfacings, and Zakrzewska et al [42], who also tested nickel coating but deposited by the different method (the electroless method). With increasing testing time to 60 min, the volume loss increased to 0.22, 0.06 and 0.15 mm 3 , respectively for the uncoated steel, Nickel 1 and Nickel 2 coating.…”
Section: Cavitation Erosion Testsmentioning
confidence: 71%
See 1 more Smart Citation
“…9a). Very short as well as the lack of incubation period was also noted by Li et al [53], who tested 316L steel, Wantang et al [54], who tested martensitic HNS steel and two CrNiMo stainless steel grades, Liu et al [55], who tested Cr-Mn-N steels, Szala [56], who tested the NiCrSiB hardfacings, and Zakrzewska et al [42], who also tested nickel coating but deposited by the different method (the electroless method). With increasing testing time to 60 min, the volume loss increased to 0.22, 0.06 and 0.15 mm 3 , respectively for the uncoated steel, Nickel 1 and Nickel 2 coating.…”
Section: Cavitation Erosion Testsmentioning
confidence: 71%
“…Taking into account the properties of nickel coatings, the 43% higher hardness of the Nickel 1 coating compared to the Nickel 2 coating resulted in a 2.6 times lower final erosion rate despite the net of cracks. The effect of hardness on erosion resistance has been observed many times [56,59]. The presented test results showed that the erosion rate of the Nickel 2 coating was lower than that of the substrate despite the lower hardness of Nickel 2 compared to that of the substrate.…”
Section: Cavitation Erosion Testsmentioning
confidence: 82%